Miejsce antropologiczne w Ogrodach polskich Wojciecha Prażmowskiego - Ślósarska, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
Paper is devoted to the anthropology of a gardener regarded within the context of metonymic and metaphoric activity of a postmodern subject; in theoretical perspective it discusses Gellner’s conception of the “symmetrical” and “asymmetrical” cultures. A set of photographs by Wojciech Prażmowski is a direct object of analysis (Ogrody polskie, Exhibition in the City Galery of Art, Częstochowa 2001, documented also in a book edition). Photographic conceptualization of Prażmowski is an outstanding testimony of the change within anthropological and artistic paradigms of considering the topic of garden and gardener, which enables the construal of a wider social and communicational diagnosis of the changes within contemporary culture.